2011
DOI: 10.1002/jrs.2945
|View full text |Cite
|
Sign up to set email alerts
|

Frohlich interaction and associated resonance enhancement in nanostructured copper oxide films

Abstract: Nanostructured copper oxide films were prepared by the oxidation of copper films by thermal evaporation of metallic copper. Analysis of HRTEM images showed that the films of Cu 2 O and CuO phases had. The band gap of the nanostructured sample of Cu 2 O was suitable for resonance scattering by intraband Fröhlich interaction in this sample. Micro-Raman studies revealed an intense resonance Raman peak corresponding to a forbidden mode of Cu 2 O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 43 publications
(63 reference statements)
4
13
0
Order By: Relevance
“…Note that several Raman peaks in the region of 50–850 cm ‐1 are distinct and enhanced with the application of 488 nm. The result can be explained by the fact that the 488 nm excitation (2.54 eV) is in near‐resonance with the band gap energy of the Cu 2 O film, then the selection rule is broken and the Raman signal reveals large enhancement . Therefore, all of the Raman data show typical phonon vibrations of Cu 2 O crystal and support the formation of Cu 2 O, which is also in agreement with the XRD experiments.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Note that several Raman peaks in the region of 50–850 cm ‐1 are distinct and enhanced with the application of 488 nm. The result can be explained by the fact that the 488 nm excitation (2.54 eV) is in near‐resonance with the band gap energy of the Cu 2 O film, then the selection rule is broken and the Raman signal reveals large enhancement . Therefore, all of the Raman data show typical phonon vibrations of Cu 2 O crystal and support the formation of Cu 2 O, which is also in agreement with the XRD experiments.…”
Section: Resultssupporting
confidence: 79%
“…The Raman spectrum at a temperature of 77 K is chosen for the frequency studies and the features generating from zone‐center phonon are identified as follows: Γ 25− (81 cm ‐1 ), Γ 12− (106 cm ‐1 ), Γ 15− (1) (longitudinal‐optical (LO)‐phonon frequency, 150 cm ‐1 ), 2Γ 12− (215 cm ‐1 ), 2Γ 15− (1) (304 cm ‐1 ), 4Γ 12− (415 cm ‐1 ), Γ 25+ (505 cm ‐1 ), Γ 15− (2) (transverse‐optical (TO)‐phonon frequency, 632 cm ‐1 ; LO, 655 cm ‐1 ), Γ 15− (1) (LO) + Γ 15− (2) (LO) (810 cm ‐1 ). The sharp peaks of the infrared‐allowed mode Γ 15− (1) (LO, 151 cm ‐1 ) and second‐order overtone 2Γ 12− (215 cm ‐1 ) indicate the existence of strong electron–phonon coupling mediated by Fröhlich interaction in the film composed of the Cu 2 O phase . Other weak scattering from Raman forbidden first‐order modes such as those at 106, 632, and 655 cm ‐1 could be due to intrinsic selection rule violation mechanisms in pure Cu 2 O crystal .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Surface profile measurements of the sample using a Dektak profilometer indicated that these micro-bubble features vary in height from approximately 1 lm to 5 lm, with the regions between the micro-bubbles comprising a flat planar film, as is expected for a CuO film formed directly upon the flat underlying sapphire substrate. , and when probed with an excitation energy of 1.96 eV at 300 K, the dominant signal 31 is the A g mode at 298 cm…”
Section: Resultsmentioning
confidence: 99%
“…They reported that free dipyrrins should find applications in all areas of Raman spectroscopy including fundamental studies of the mechanisms of SERS and bioanalytical and environmental applications. Mohemmed Shanid and co‐workers studied the Fröhlich interaction and associated resonance enhancement in nanostructured copper oxide films . The band gap of the nanostructured sample of Cu 2 O was suitable for resonance scattering by intraband Fröhlich interaction.…”
Section: Resonance Raman Spectroscopymentioning
confidence: 99%